The Impact of Psychological Well-Being and Work Flexibility on Millennial Talent Retention in Companies - Siti Normi (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Changes in workforce demographics indicate that millennials now dominate the labor market, creating new challenges for organizations in retaining talent from this generation. Millennials possess distinctive characteristics, including a strong emphasis on work–life balance, meaningful work, and a work environment that supports psychological well-being. Consequently, talent retention strategies must be aligned with their values and expectations. This study aims to analyze the influence of psychological well-being and work flexibility on millennial talent retention in organizations. The research employs a qualitative approach using a literature review method by examining relevant journal articles, academic books, and research reports. Data were analyzed through thematic analysis to identify patterns and relationships among variables. The findings indicate that psychological well-being plays a crucial role in enhancing organizational commitment and reducing turnover intention among millennial employees. In addition, work flexibility is shown to increase job satisfaction, work–life balance, and employee loyalty. The results also reveal that the combination of psychological well-being and work flexibility produces a synergistic effect that strengthens millennial talent retention. Therefore, organizations are encouraged to integrate psychological well-being initiatives and flexible work policies into their human resource management strategies.